EULAR points to consider for conducting clinical trials in systemic lupus erythematosus: literature based evidence for the selection of endpoints. Issue 4 (23rd April 2008) - Bertsias, G K; Ioannidis, J P A; Boletis, J; Bombardieri, S; Cervera, R; Dostal, C; Font, J; Gilboe, I M; Houssiau, F; Huizinga, T; Isenberg, D; Kallenberg, C G M; et al.
Abstract : Objective: To assess available evidence on the use of end-points (outcome measures) in clinical trials in systemic lupus erythematosus (SLE), as a part of the development of evidence-based recommendations for points to consider in clinical trials in SLE. Methods: The European League Against Rheumatism (EULAR) Task Force on SLE comprised 19 specialists, a clinical epidemiologist and a research fellow. Key questions addressing the evidence for clinical trial end-points in SLE were compiled using the Delphi technique. A systematic search of the PubMed and Cochrane Library databases was performed using McMaster/Hedges clinical query strategies and an array of relevant terms. Evidence was categorised based on sample size and type of design, and the categories of available evidence were identified for each recommendation. The strength of recommendation was assessed based on the category of available evidence and agreement on the statements was measured across the 19 specialists. Results: Eight questions were generated regarding end-points for clinical trials. The evidence to support each proposition was evaluated. The literature review revealed that most outcome measures used in phase 2/3 trials in SLE have not been formally validated in clinical trials, although some indirect validation has been undertaken. Conclusion: This systematic literature review forms the evidence base considered in the development of the EULAR recommendations for end-points in clinical trials in SLE.